The Effect of Loose Parts on the Development of Early Childhood Creativity - Marisa Sardi; Farida Mayar (STAI Hubbulwathan Duri, 2023)
Creativity is a child's ability that should be developed early on. Loose parts are open items which are easily found in the daily environment. This research was conducted at TK PAUD Seulanga Meuligoe Selatan. This study aims to describe learning outcomes with loose part activities that can affect children's creativity. Case study research is a type of qualitative research that was used by the researchers in this study. Children between the ages of 0 and 5 are the focus of this study. Observation, short conversations, and keeping records are all ways that data are gathered. The results of a study show that kids can be more creative when they do loose-part tasks. Children learn to be active, creative, and curious when they build with loose parts. They also learn how to fix problems. From previously, children only reached undeveloped (BB) and started to develop (MB) levels to growing as expected (BSH) and very well developed (BSB). Besides that, loose part activities make children recognize objects around their environment.